Rekonstruksi Penegakan Sanksi Pidana Terhadap Justice Collaborator dalam Perspektif Kepastian Hukum dan Keadilan - Hassanain Haykal (LPPM Universitas Ekasakti Padang, 2023)
Law enforcement is an important aspect of a legal system, where a good law enforcement will achieve the rule of law. Law enforcement cannot be separated from enforcing sanctions and procedural enforcement. In the realm of criminal law, the enforcement of sanctions against perpetrators of criminal acts should be in accordance with the norms that set out in statutory regulations and fulfill the legal certainty and justice. However, enforcement of sanctions must also consider certain reasons that cause criminal sanctions to fulfill a sense of justice without eliminating the certainty of law, one of which is the enforcement of sanctions against Justice Collaborators. For this reason, it is necessary to reconstruct the enforcement of criminal sanctions against Justice Collaborators. The research methods used in this paper is Normative Juridical, with a conceptual approaches, cases and statutory approach, with the theory of legal certainty and justice. Based on this, the reconstruction that can be carried out is to determine the amount of imprisonment in the statutory regulations toward Justice Collaborators by providing leniency (imprisonment) as much as half of the maximum sanction from the article charged.